2004
DOI: 10.1212/01.wnl.0000115122.81621.fe
|View full text |Cite
|
Sign up to set email alerts
|

Does magnetoencephalography add to scalp video-EEG as a diagnostic tool in epilepsy surgery?

Abstract: MEG is most useful for presurgical planning in patients who have either partially or nonlocalizing V-EEG results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 27 publications
4
68
0
2
Order By: Relevance
“…No spike averaging was performed. The location, orientation, and strength of dipole sources that best fit the measured magnetic fields were calculated using the SECD model (Stefan et al, 2003;Pataraia et al, 2004). The following statistics criteria were used when reviewing the SECD results: goodness of fit 480%, confidence volume 51000 mm 3 , reduced 2 5 1.5, and dipole moment between 100-500 nAm.…”
Section: Megmentioning
confidence: 99%
“…No spike averaging was performed. The location, orientation, and strength of dipole sources that best fit the measured magnetic fields were calculated using the SECD model (Stefan et al, 2003;Pataraia et al, 2004). The following statistics criteria were used when reviewing the SECD results: goodness of fit 480%, confidence volume 51000 mm 3 , reduced 2 5 1.5, and dipole moment between 100-500 nAm.…”
Section: Megmentioning
confidence: 99%
“…Several studies have shown that this method can provide reliable and useful information in presurgical patients with partial epilepsy (Stefan et al, 2003;Wu et al, 2006;RamachandranNair et al, 2007), and have concluded that non-invasive MEG techniques might eventually partly replace invasive intracranial recording techniques (Pataraia et al, 2004;Papanicolaou et al, 2005;Knowlton et al, 2006). However, the analysis procedures require that each dipole is manually reviewed and classified as either corresponding to a real spike or as corresponding to a non-epileptic origin, which can be timeconsuming, requires trained and experienced scorers, and introduces a sizeable amount of subjectivity in the results.…”
Section: Introductionmentioning
confidence: 99%
“…The localization of the origin of interictal epileptiform discharges (IEDs) plays a major role in the presurgical work-up of patients with focal refractory epilepsy, especially, using MEG (Englot et al, 2015;Knowlton, 2008;Ossenblok et al, 2007;Pataraia et al, 2004;Stefan et al, 2003) and more recently simultaneous EEG and fMRI (Thornton et al, 2010;Zijlmans et al, 2002). Nowadays the identification of the network underlying the IEDs is an auxiliary tool for the question where to place an intracortical grid or stereotactic depth electrodes for presurgical evaluation in refractory candidates (Pataraia et al, 2004;Schulz et al, 2000;van Houdt et al, 2013van Houdt et al, , 2012Walczak et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays the identification of the network underlying the IEDs is an auxiliary tool for the question where to place an intracortical grid or stereotactic depth electrodes for presurgical evaluation in refractory candidates (Pataraia et al, 2004;Schulz et al, 2000;van Houdt et al, 2013van Houdt et al, , 2012Walczak et al, 1990). Furthermore, the presence of localized IEDs has been employed to differentiate between the type of epilepsy (focal or generalized) in relation with post surgical outcome (Holmes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%